Distribution patterns of fishes in the head region of a turbid Eastern Cape estuary - Ter Morshuizen, Leslie David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
Two and a half years of data were collected from the Great Fish River and estuary using seine nets and gill nets to determine the fish species composition within these regions. The head region of the Great Fish River estuary was found to have a rich fish fauna, with the euryhaline marine fish component totally dominating the catch in all three regions. Gilchristella aesiuaria was the single most common species and several euryhaline marine species were captured in freshwater for the first time. Physical parameters were also measured in an effort to ascertain the possible factors which may affect the distribution and length frequency of the most common species within this area. Salinity was found to be the single most important factor affecting the species composition, and the sampling area was consequently divided into three regions, viz. river (< I "°), head (1-4 "°) and estuary (> 4 "°). In addition, it was determined that river flow rate during the month prior to sampling also had a profound effect on species composition in all three regions. Based on the available evidence it is suggested that for most species this is related to conductivity levels rather than flow per se.
Keywords: Fishes -- South Africa -- Eastern Cape -- Great Fish River -- Geographical distribution